2021
DOI: 10.36909/jer.v9i1.8603
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of combustion of palm kernel shell and coconut husk blend in a pilot-scale grate furnace

Abstract: Pollution resulting from the use of stereotypical fuels for energy generation has been a great menace to the air we breathe. Co-combustion of biomass fuels has proved effective against the deficiencies associated with the burning of individual biomass on its own. This study aimed at investigating the combustion of Palm Kernel Shell (PKS) and Coconut Husk (CH) blend in a grate furnace. The proximate and ultimate analyses of the mix of PKS and CH were determined using ASTM 3174-76 method. Four combustion tests w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Apart from the usage of palm kernel shell as filler in composites, Oladosu et al (2021) investigated the combustion of palm kernel shell with coconut shell in grate furnace. From the analysis, they found that palm kernel shell burns effectively with coconut husk and creates a significant effect on temperature and emission characteristics of the biofuel.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the usage of palm kernel shell as filler in composites, Oladosu et al (2021) investigated the combustion of palm kernel shell with coconut shell in grate furnace. From the analysis, they found that palm kernel shell burns effectively with coconut husk and creates a significant effect on temperature and emission characteristics of the biofuel.…”
Section: Introductionmentioning
confidence: 99%